A privacy-preserving reputation scheme for trust management on VANETs applications - Jaimes, Luz Marina Santos (2017)
Vehicles will use pseudonyms instead of relying on long-term certificates to provide security and privacy. Pseudonyms are short-term public key certificates that do not contain identity-linking information about the vehicle. However, there is a constant risk that authorised vehicles may send fake messages or behave selfishly, and this can affect the performance of the Vehicular Ad hoc NETwork (VANET). In this context, trust management is another important component of security services in VANETs, which provides a unified system for establishing a relationship between the nodes and helps by keeping record of the behaviour of the vehicles. Nevertheless, it is a challenging task to monitor the evolving pattern of the vehicular behaviour, since communication between the vehicles is anonymous. It is not easy to find a balanced solution that meets the requirements of security, privacy, and trust management in VANET. In view of this, we put forward a Preserving-Privacy Reputation Scheme (PPRS) applied to VANETs, in which a reputation server through a Roadside Unit receives feedback about the behaviour of the vehicles. The server updates and certifies the reputation of the vehicles by matching their anonymous identities with their real ones. Our scheme introduces geographical areas of security, in which the security of an area can be adapted to higher or lower levels depending on the reputation of the vehicles. In addition, complex reputation is examined, in which the reputation of a vehicle is linked to several behavioural factors. A further key area that is explored is the performance evaluation of PPRS which is conducted through a set of simulations in a grid scenario, based on an opportunistic message forwarding application. The results showed the effectiveness of PPRS in terms of assessing the behaviour of the vehicles and taking measures against the misbehaving vehicles. We used SUMO to simulate the mobility model; OMNET++ and Veins supported the simulation of the network model. In addition, Crypto++ was used to implement the elliptical curve cryptographic functions of signature and verification of messages, as recommended by the security standards. Finally, we employ a pseudonym changing strategy in which the reputation is discretised at two levels of reputation. The strategy was implemented in a realistic traffic simulation scenario, and was compared with the so called status and synchronous strategies through a serie of simulations. The results showed that the number of pseudonyms used in our strategy is lower than the strategies mentioned above, and maintains the rate of success of changing pseudonym achieved by the synchronous strategy.